Efficacy of romiplostim in treatment of thrombocytopenia in children with Wiskott–Aldrich syndrome. (31st October 2020) - Khoreva, Anna; Abramova, Irina; Deripapa, Elena; Rodina, Yulia; Roppelt, Anna; Pershin, Dmitry; Larin, Sergey; Voronin, Kirill; Maschan, Alexey; Novichkova, Galina; Shcherbina, Anna
Summary: Wiskott–Aldrich syndrome (WAS) is a life‐threatening primary immunodeficiency associated with bleeding of variable severity due to thrombocytopenia. Correction of the thrombocytopenia is of paramount importance for most WAS patients. We report a retrospective analysis of the safety and efficacy of romiplostim treatment in reducing thrombocytopenia and bleeding tendency in 67 children (median age 1·3 years) with genetically confirmed WAS, followed in eight months (range, 1–12 months). Complete or partial primary responses regarding platelet counts were observed in 22 (33%) and 18 (27%) subjects, respectively. Yet, even in the non‐responder group, the risk of haemorrhagic events decreased significantly, to 21%, after the first month of treatment. The responses tended to be durable and stable over time, with no significant fluctuations in platelets counts. The results of this retrospective study of a large cohort of WAS patients demonstrates that romiplostim can be used to increase platelet counts and reduce the risks of life‐threatening bleeding in WAS patients awaiting haematopoietic stem cell transplantation or forgoing the procedure for various reasons.